Lineage, territory and image in Ramal by Cynthia Rimsky - Alcívar Bellolio, Daniela (2022)
This paper analyzes the novel Ramal (2011), by Cynthia Rimsky, searching for the particular relationships between space and image. On the one hand, the material characteristics of photographic images in the novel are analyzed to understand how they dialogue with, and intervene in, the configuration of the verbal narration and its particular tones and operations of display and invisibility. On the other hand, landscape is thought of as a fundamental device for the narrative policy of the novel. The main object of this article is the articulation developed by these two devices in order to generate an ambiguous and problematic characterization of the protagonist’s genealogy.